Comparison of methods for measurement of somatic cell count in goat milk: somatic cells - Zazharska, NM (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of the study was to compare the efficiency of determining the number of somatic cell count in goat milk by different methods. Somatic cells in individual samples of milk from 28 goats were studied using analyzers "Somatos", "SomaCount Flow Cytometer" and by the counting method in milk films stained according to Romanovsky – Giemsa, May-Grünwald and with pyronin Y. For the counting of somatic cells in goat milk by Prescott and Breed method, it is recommended to stain milk films by the May-Grünwald method, because the cytoplasm and nuclei of somatic cells are clearly stained, and the cost of dyes is much less than the pyroninY method. When counting cells in milk films stained by any method, no samples with the SCC up to 100 ´ 103 cells/ml were found. Direct counting of somatic cells in milk films stained by any method reveals a greater number of cells than with the help of devices. It was found that the fat content in goat milk with SCC >3000 ´ 103 cells/ml is significantly higher (P < 0.05) compared to milk with SCC < 1000 ´ 103 cells/ml. The quality of goat’s milk smears for counting of somatic cells quantity stained by the May-Grünwald method corresponds to the recommended method with pyronin Y, and the cost of dyes is 28.4 times lower. The distribution of somatic cell ranges is similar between different methods of staining smears, which once again proves the accuracy of the method of direct cell counting in milk films, although it is more labor-intensive than hardware methods.